The Realization of Yoga Therapy In The Complex Rehabilitation Of Patients After Myocardial Infarction - Indyka, Svitlana; Bielikova, Nataliia; Ulianytska, Nataliia; Andrijchuk, Olga; Tomaschuk, Olena; Pavlyshyna, Nataliia (My University, 2017)
The evaluation of persons’ life quality after myocardial infarction, temperament correction and intensity of their personal reactions to the disease are an integral part of the rehabilitation process. The goal of the research lies in the description of the effects of the author's rehabilitation program with elements of yogic breathing on the life quality of the patients after myocardial infarction in follow-up period. The patients of the main group were engaged in the author's rehabilitation program; the comparison group took a cure of conventional rehabilitation scheme in Ukraine. The effectiveness of the rehabilitation programs was determined by the quality of live indicators through standardized method "Quality of Life in Cardiovascular Disease." As part of study found, the positive dynamics on the total life quality was observed in both groups of patients. It should be noted that 76.7% of patients in the main group hadn’t considered their lives invalid by the end of the study. But only 60% of patients had this figure in the comparison group. The sources of patients’ anxiety caused by this pathology were analyzed, and the tetrad of reasons that caused the maximum reduction in quality of life, was found out, namely: the need for treatment, restriction of physical efforts, and emotional stress, reduce vitality in daily life.
Keywords: myocardial infarction; life quality; rehabilitation program